HUBUNGAN ANTARA BIMBINGAN KARIR SMK 17 AGUSTUS 1945 SEMARANG - Wahyu Hidayat; Alice Zellawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2024)
Career decisions among students are the individual's awareness and need to make career choices, both in choosing majors in general secondary schools and various alternatives related to higher education that are job/occupation oriented. Career guidance is a device, more precisely a systematic program, process, technique, or service in order to help individuals to understand and accept an image of their personal self and an image of the world of work outside themselves, bringing this self-image into harmony with the world of work that ultimately can choose a field of work, enter it and build a career in that field. The hypothesis proposed in this research is that there is a positive relationship between career guidance and career decisions. This research involved 138 respondents who were class XI students at SMK 17 August 1945 Semarang. The non-parametric Spearman-rho correlation test produces a coefficient of +0.293 with a correlation significance level of 0.000, so this research hypothesis is accepted. The career guidance variable has an effective contribution of 7% to the career decision variable for students at SMK 17 August 1945 Semarang. While the remaining 93% is influenced by other factors. Keywords: Career decisions, career guidance